Accelerated Age-Related Arterial Stiffness in Systemic Lupus Erythematosus Patients. Issue 8 (December 2016) - Ding, Fa ming; Li, Mengtao; Yang, Xinglin; Ye, Yicong; Kang, Lin; Pang, Haiyu; Wang, Qian; Xu, Dong; Zeng, Xiaofeng; Zhang, Shuyang
Abstract : Background: An increased prevalence of arterial stiffness in systemic lupus erythematosus (SLE) patients has been established, but the mechanisms of progression of arterial stiffness with increasing age have not been fully explored. Objectives: To investigate age-related progression of arterial stiffness among SLE patients relative to healthy controls. Methods: A total of 161 female SLE patients who were enrolled in the Chinese SLE Treatment and Research group (CSTAR) registry and 135 age-matched healthy control subjects participated in this cross-sectional investigation. Traditional cardiovascular risk factors and SLE-related parameters were assessed on the day that brachial-ankle pulse wave velocity (baPWV) was examined. SAS 9.3 was used to perform all statistical analyses in this study. Linear regression and curvilinear regression models were utilized to analyze the association between age and arterial stiffness. Results: Arterial stiffness based on baPWV significantly differed between the SLE patients and controls in the different age groups, and within the SLE group. The baPWV increments for each age group (<25, 25–34, 35–45, and >45) were 30 cm/s, 52 cm/s, and 121 cm/s for the controls and 61 cm/s, 132 cm/s, and 155 cm/s for the SLE patients, respectively. Curvilinear regression and linear regression revealed various trends of increased arterial stiffness among the SLE patients compared with the healthy controls. The correlation coefficients between age and arterial stiffness significantly differed among the SLE patients relative to the healthy controls (correlation coefficients of 0.46478 and 0.52612, respectively; t = 2.05; P = 0.0409). Multivariate analysis revealed that age, mean blood pressure (BP) ( P < 0.0001), erythrocyte sedimentation rate (ESR) ( P = 0.0073), prednisone course ( P = 0.0144), and SLE disease activity ( P = 0.0405) were associated with arterial stiffness among the SLE patients. Further, these patients exhibited earlier exposure to and higher frequencies of several risk factors compared with the controls in each age group (<25 years: OR = 6.3253; 25–34 years: OR = 3.1043; 35–45 years: OR = 3.1316; >45 years: OR = 3.6020). Conclusions: The mechanisms of the age-related progression of arterial stiffness differed among the SLE patients relative to the healthy controls. Furthermore, accelerated arterial stiffness was observed among the SLE patients relative to the healthy controls with advancing age.